A hybrid prognostic methodology for tidal turbine gearboxes. (December 2017) - Elasha, Faris; Mba, David; Togneri, Michael; Masters, Ian; Teixeira, Joao Amaral
Abstract: Tidal energy is one of promising solutions for reducing greenhouse gas emissions and it is estimated that 100 TWh of electricity could be produced every year from suitable sites around the world. Although premature gearbox failures have plagued the wind turbine industry, and considerable research efforts continue to address this challenge, tidal turbine gearboxes are expected to experience higher mechanical failure rates given they will experience higher torque and thrust forces. In order to minimize the maintenance cost and prevent unexpected failures there exists a fundamental need for prognostic tools that can reliably estimate the current health and predict the future condition of the gearbox. This paper presents a life assessment methodology for tidal turbine gearboxes which was developed with synthetic data generated using a blade element momentum theory (BEMT) model. The latter has been used extensively for performance and load modelling of tidal turbines. The prognostic model developed was validated using experimental data. Highlights: A prognostic Model has been developed to predict the residual life of tidal turbines gearbox. The model employed synthetic turbulence data generated for The Ramsey Sound region. The result shows life variations between the gears. The model was validated using test data.